2023
DOI: 10.1213/ane.0000000000006425
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obstructive Sleep Apnea With Postoperative Delirium in Procedures of Moderate-to-High Complexity: A Hospital-Registry Study

Abstract: BACKGROUND: Patients suffering from obstructive sleep apnea (OSA) experience chronic sleep disturbances and desaturation, factors that have been associated with postoperative delirium and that can be aggravated after anesthesia for complex procedures. We investigated whether OSA is associated with delirium after anesthesia, and whether this association is modified by procedural complexity. METHODS: Hospitalized patients ≥60 years who underwent general anesthesia or procedural sedation for procedures of moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…4,6,13 This time frame for the development of delirium was selected based on clinical relevance and previous literature. 8,14,15 Driven by an inflammatory surge and residual effects of anesthesia, 16 patients are at particularly high risk of postoperative delirium during the first 7 postoperative days. 17 Further details on the definition of the primary outcome and on how delirium was diagnosed at our institution are provided in Supplemental Digital Content 1 (section S1.2, https://links.lww.com/ALN/D310).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,6,13 This time frame for the development of delirium was selected based on clinical relevance and previous literature. 8,14,15 Driven by an inflammatory surge and residual effects of anesthesia, 16 patients are at particularly high risk of postoperative delirium during the first 7 postoperative days. 17 Further details on the definition of the primary outcome and on how delirium was diagnosed at our institution are provided in Supplemental Digital Content 1 (section S1.2, https://links.lww.com/ALN/D310).…”
Section: Methodsmentioning
confidence: 99%
“…4,6,13 This time frame for the development of delirium was selected based on clinical relevance and previous literature. 8,14,15…”
Section: Exposure and Outcome Measuresmentioning
confidence: 99%
“…2,3 Sleep disorders are critical risk factors among the various risk factors for DNR after surgery. [4][5][6] Meanwhile, aging is an independent risk factor for sleep disorders. 7 Preclinical studies have shown that sleep disorders aggravate cognitive impairment after surgery in older adult mice but not in adult mice, suggesting that aging is more sensitive to sleep disorders and may contribute to DNR.…”
mentioning
confidence: 99%
“…2,12,13 However, no study has explored the specific risk factors for DNR in patients with preoperative sleep disorders. Considering the relationship between sleep and postoperative cognitive function, especially in older adult patients, 3,6,14,15 it is necessary to link these 2 main risk factors (preoperative sleep disorders and DNR) that impair the perioperative brain health to explore potential biomarkers.…”
mentioning
confidence: 99%